Analysis Of The Letter Jar In Surah Al-Hujurat And Its Learning Media - Amrulloh, Akmal Varras; Zuhriyah, Luthfiyatuz; Muntadziroh, Tsalitsa Nuurun; Rahayu, Siska; Fatkhurrohman, Fatkhurrohman; Aqidho, Yoga Ayudha (DAS Institute, 2023)
This research aims to find out the meaning of the letter jar in Surah Al-Hujarat, as well as determine the appropriate media for learning the letter jar. In this research, library research is used. This research is characterized as qualitative because the research object is learning media which is explained using descriptive words so that it can be understood easily. Based on data analysis that has been carried out on surah AL-Hujarat, there are 44 words containing the letter jar, with 7 types of jar letters, namely: من , ب, ل, في, على, لى, ك. Therefore, the appropriate media for learning jargon is visual media.